Conceptual Space of Kazakhstani Media Discourse: Psycholinguistic Aspects of Approach (Eurasian Journal of Philology Science and Education, 2020)
The article provides an analysis of the conceptual space of the Kazakhstan media discourse. Cognitive, discursive-analytical, sociological, historical and political scientific theories in this linguistic study complement each other, have an explanative power. The concepts of power, ideology and history are defined in the framework of the theory of critical discourse analysis as the basic concepts of Kazakhstan discourse. The research paradigm of analyzing the problems of the correlation of conceptual space, discourse and identity is presented in the work within the framework of the semiotic theory: from communication processes to the sphere of generation of texts. In this work, psycholinguistic methods have revealed the meaningful filling of the conceptual space in the associative-verbal network of native speakers. The archaization of consciousness revealed in the study is not so much a return to the old as a restoration of the old based on the knowledge and ideas about the past that are popular. This is revealed when referring to samples of mass consciousness reflected in associative fields to the same stimulus words of the Russian and Kazakh languages. The novelty of the work is determined by the material and methodology of analysis, in which the postulates of cognitive theories are supported by the achievements of critical discourse analysis. The main results of the work are designated cognitive strategies of the medial space. It is proved in the work that Sovietism is currently acting as a system-forming component of the Kazakh-speaking and Russian-speaking discourse of the country. Three distinguished projects: Eurasian, Pan-Turkic and liberal – are the same intertext that defines the political, social and cultural boundaries and preferences of the whole Kazakhstani society, as a result and discursive practice. Projects have their own historical past, determine real politics and find their medial reflection.